2015
DOI: 10.1016/j.ecoleng.2014.09.097
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the water saturation level on phosphorus retention and treatment performances of vertical flow constructed wetland combined with trickling filter and FeCl3 injection

Abstract: International audienceThe aim of the study was to determine the effects on treatment efficiency of oxidation-reduction (redox) conditions that are caused by different water saturation levels within vertical-flow constructed wetlands (VFCW), with specific attention to phosphorus (P) retention. The study was conducted by monitoring over 18 weeks a pilot-scale system consisting of a biological aerobic trickling filter as a biological pre-treatment step, followed by ferric chloride (FeCl3) addition for phosphate r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…The concentration of Fe(II) increased with addition of increasing levels of carbon source. Eh may affect microbial processes and the fate of ferric species (Kim et al, 2014). A negative correlation was observed between the concentrations of S and Fe(II) when the Eh exceeded 80 mV of the system (Fig.…”
Section: Secondary Fixation Of As With Fe and S In A Reducing Environmentioning
confidence: 91%
See 1 more Smart Citation
“…The concentration of Fe(II) increased with addition of increasing levels of carbon source. Eh may affect microbial processes and the fate of ferric species (Kim et al, 2014). A negative correlation was observed between the concentrations of S and Fe(II) when the Eh exceeded 80 mV of the system (Fig.…”
Section: Secondary Fixation Of As With Fe and S In A Reducing Environmentioning
confidence: 91%
“…In aquatic ecosystem restoration, iron chloride (FeCl 3 ) is widely used for improving water clarification or used as a flocculant to remove contaminants such as phosphorus, Cu, Pb, Zn and arsenic (As) from water (Contin et al, 2015;Kim et al, 2014) by co-precipitation of both constituents as contaminant-containing iron (oxyhydr)oxides (Zaaboub et al, 2014), and transfer contaminants from water into sediments. However, some researches showed that iron (hydr)oxides precipitated during sewage sludge flocculation were partially redissolved the acid soil, releasing previously surface adsorbed contaminants (Contin et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, ferric chlorides are effective as primary coagulants due to their associative character in solution. At controlled concentrations, it is excellent for both drinking and wastewater treatment applications, including phosphorus removal, 51 sludge conditioning, and struvite control. 52,53 It also prevents odor and corrosion by controlling hydrogen sulfide formation.…”
Section: Ion Rejection Efficiencymentioning
confidence: 99%
“…Similarly, the feedback from 5 years of data obtained from "compact VSSF CWs" showed that this system met the French standards and outperformed the first stage of "classical VSSF CWs". Kim et al (2015) conducted an 18-week study in a pilot-scale wastewater treatment system consisting of a biological aerobic trickling filter as a biological pre-treatment step, followed by the addition of ferric chloride (FeCl 3 ) for phosphate removal and a stage of VSSF CW in France. The aim was to determine the effects on treatment efficiency of oxidation-reduction (redox) conditions caused by different water saturation levels within the VSSF part, with specific attention to P retention.…”
Section: This Special Issuementioning
confidence: 99%